The Effect of a Digital Flipbook Integrated with Gamified Wordwall Assessments on Learning Motivation and Outcomes in Islamic Education - Maulana Paramaditya Ananta; Miftah Hur Rahman Zh; Naufal Rifqi Nasution; Muhammad Arinal Haq (NAJAHA, 2025)
This study provides compelling empirical evidence for the effectiveness of integrating digital learning media with gamified assessment tools in the context of Islamic secondary education. Addressing a clear research gap regarding the combined impact of such technologies in Al-Quran Hadits instruction, the researchers employed a quasi-experimental design with 68 eleventh-grade students at MAN Kota Batu. The experimental group utilized a digital flipbook for content delivery, reinforced by a series of Wordwall-based gamified assessments, including quizzes and matching games. The control group, in contrast, received instruction through conventional textbooks. The study’s findings were statistically significant and robust. The experimental group exhibited substantially higher learning motivation, with a mean score of 82.47 compared to 71.35 in the control group, representing a large effect size. Furthermore, their learning outcomes were markedly superior, with a mean score of 84.56 versus 72.18, also demonstrating a very large effect size. A MANOVA analysis confirmed a significant multivariate effect, indicating that the treatment had a powerful positive influence on the combined dependent variables of motivation and achievement. These results suggest that the interactive and engaging nature of the digital flipbook, combined with the immediate feedback and game-like elements of Wordwall, creates a more stimulating and effective learning environment. The study offers crucial quantitative evidence for educators and policymakers in madrasahs, supporting the strategic integration of technology to enhance both student engagement and academic performance in religious studies.